Supplementation and therapeutic use of vitamin D in patients with multiple sclerosis: Consensus of the Scientific Department of Neuroimmunology of the Brazilian Academy of Neurology - Doralina Guimarães Brum; Elizabeth Regina Comini-Frota; Claúdia Cristina F. Vasconcelos; Elza Dias-Tosta (Arquivos de Neuro-Psiquiatria)
Multiple sclerosis (MS) is an inflammatory, autoimmune, demyelinating, and degenerative central nervous system disease. Even though the etiology of MS has not yet been fully elucidated, there is evidence that genetic and environmental factors interact to cause the disease. Among the main environmental factors studied, those more likely associated with MS include certain viruses, smoking, and hypovitaminosis D. This review aimed to determine whether there is evidence to recommend the use of vitamin D as monotherapy or as adjunct therapy in patients with MS. We searched PUBMED, EMBASE, COCHRANNE, and LILACS databases for studies published until September 9 th , 2013, using the keywords “multiple sclerosis”, “vitamin D”, and “clinical trial”. There is no scientific evidence up to the production of this consensus for the use of vitamin D as monotherapy for MS in clinical practice.